Mycobacterial interspersed repetitive unit typing and mutational profile for multidrug-resistant and extensively drug-resistant tuberculosis surveillance in Portugal: a 3-year period overview - Silva, Carla (2015)
Multidrug tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDRTB) cases constitute a serious health problem in Portugal, of which the majority of isolates belong to the Lisboa family and the Q1 cluster, highly related to the Lisboa family. Here we sought to investigate the molecular basis of resistant TB as well as to determine the prevalence of specific drug resistance mutations and their association with MDR-TB and/or XDR-TB. In total, 74 Mycobacterium tuberculosis clinical isolates collected in Lisbon Health Region were genotyped by 24-loci mycobacterial interspersed repetitive units–variable number of tandem repeats (MIRU-VNTR), and the mutational profile associated with first- and second-line drug resistance was studied. Seven new mutations were found, whilst the remaining 28 mutations had been previously associated with drug resistance. None of the mutations was specifically associated with MDR-TB. The mutational patterns observed among isolates belonging to Lisboa3 and Q1 clusters were also observed in isolates with unique MIRU-VNTR patterns but closely related to these strains. Such data suggest that the genotyping technique employed discriminates isolates with the same mutational profile. To establish the most adequate genotyping technique, the discriminatory power of three different MIRU-VNTR sets was analysed. The 15-loci MIRU-VNTR set showed adequate discriminatory power,comparable with the 24-loci set, allowing clustering of 60% and 86% of the MDR-TB and XDR-TB isolates, respectively, the majority of which belonged to the Lisboa3 and Q1 clusters. From an epidemiological standpoint, this study suggests combined mutational and genotyping analysis as a valuable tool for drug resistance surveillance.